Pleisticanthoides Yokoya, 1933, a valid genus of deep-sea inachid spider crabs (Crustacea: Decapoda: Brachyura: Majoidea), with descriptions of two new species from the Philippines, Papua New Guinea and Vanuatu - Ng, Peter K. L.; de Forges, Bertrand Richer (Zootaxa, 2012)
The inachid spider crab genus Pleisticanthoides Yokoya, 1933, is revalidated and removed from the synonymy ofPleistacantha Miers, 1879, distinguished by the absence of strong spines on the carapace (with only spinules or setae),unarmed pereiopods (with only stiff setae along margins and not spines), possession of a relatively longer, more slenderocular peduncle with a smaller cornea, slender adult male chelae, and a gently curved male first gonopod which has thedistal part dorsoventrally flattened and without a subdistal process. Three species are recognised from the Indo-WestPacific region: Pleisticanthoides simplex (Rathbun, 1932) (= Pleisticanthoides nipponensis Yokoya, 1933) from Japan, P. cameroni n. sp. from the Philippines, and P. piccardorum n. sp. from Vanuatu and Papua New Guinea.